Genetic alterations in epidermal growth factor receptor-tyrosine kinase inhibitor-naïve non-small cell lung carcinoma - Yamaura, Takumi (Oncol Lett, 2020)
Epidermal growth factor receptor (EGFR)-tyrosine kinase inhibitors (TKIs) are an approved first-line therapy against unresectable or advanced non-small cell lung cancer (NSCLC) harboring EGFR gene activating mutations. However, the majority of tumors develop acquired resistance against EGFR-TKIs and some tumors exhibit natural resistance. A number of resistance mechanisms against the latest third-generation EGFR-TKIs have been reported, including tertiary EGFR C797S mutation and several gene alterations activating EGFR or other signaling pathways. The current study aimed to identify the frequency of natural EGFR-TKI resistance in pretreatment NSCLC and to predict the therapeutic effect of EGFR-TKIs. A total of 246 EGFR-TKI-naïve NSCLC patients harboring known EGFR gene mutations were identified. The presence of EGFR C797S and T790M mutations were determined using the peptide nucleic acid-locked nucleic acid PCR clamp method. ERBB2, MET, EGFR, ALK, BRAF, FGFR1, MYC, RET, CCND1, CCND2, CDK4, CDK6, MDM2 and MDM4 gene amplification, which can lead to resistance against any generation EGFR-TKIs, was determined using the multiplex ligation-dependent probe amplification assay. No concurrent C797S mutation with known EGFR mutations were identified. T790M mutation was identified in 12 patients (4.9%). ERBB2 or MET gene amplification was found in some patients (0.0–0.4%). MDM2 gene amplification was associated with tumor recurrence and shorter progression-free survival (PFS) for first- or second-generation EGFR-TKIs. De novo EGFR C797S mutation was not identified. Other resistance mechanisms against EGFR-TKIs were indicated in some patients with EGFR-TKI-naïve NSCLC. MDM2 gene amplification, which can lead to altered cell cycle, was associated with tumor recurrence and shorter PFS in EGFR-TKI therapy.